(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Nurse retention remains a major challenge for healthcare organizations, making it essential to understand the organizational factors associated with nurses' job satisfaction. This study examined the levels of working conditions, work environment, recognition, and job satisfaction among nurses in selected hospitals in Northern Mindanao, Philippines. Specifically, it assessed the levels of these organizational factors, determined job satisfaction levels, examined their relationships with job satisfaction, and identified predictors of job satisfaction. A descriptive-correlational research design was employed, involving 174 registered nurses selected through simple random sampling from four hospitals. Data were collected using a researcher-developed questionnaire and analyzed using descriptive statistics, Spearman's rank-order correlation, and multiple linear regression. The findings revealed that nurses generally perceived their working conditions (M = 3.42), work environment (M = 3.72), recognition (M = 3.42), and job satisfaction (M = 3.52) as high. Among the dimensions of the independent variables, educational opportunity demonstrated a statistically significant positive relationship with job satisfaction (ρ = 0.155, p = .041), whereas the remaining dimensions showed no statistically significant relationships. Multiple regression analysis indicated that the combined dimensions of working conditions, work environment, and recognition did not significantly predict job satisfaction (R² = .073, F = 1.288, p = .241), suggesting that other organizational and individual factors may contribute to nurses' job satisfaction. The study concludes that although nurses generally reported favorable perceptions of their workplace and high job satisfaction, strengthening educational and professional development opportunities may further enhance job satisfaction. Future studies should examine additional organizational and personal factors that may better explain variations in nurses' job satisfaction and retention.